Activated invariant NKT cells control central nervous system autoimmunity in a mechanism that involves myeloid-derived suppressor cells - Parekh, Vrajesh V. (2013)
Invariant NKT (iNKT) cells are a subset of T lymphocytes that recognize glycolipid antigens presented by the MHC class I-related protein CD1d. Activation of iNKT cells with glycolipid antigens such as the marine sponge-derived reagent α-galactosylceramide (α-GalCer) results in the rapid production of a variety of cytokines and activation of many other immune cell types. These immunomodulatory properties of iNKT cells have been exploited for the development of immunotherapies against a variety of autoimmune and inflammatory diseases but mechanisms by which activated iNKT cells confer disease protection have remained incompletely understood. Here, we demonstrate that glycolipid-activated iNKT cells cooperate with myeloid-derived suppressor cells (MDSCs) in protecting mice against the development of experimental autoimmune encephalomyelitis (EAE) in mice, an animal model for multiple sclerosis (MS). We showed that α-GalCer induced the expansion and immunosuppressive activities of MDSCs in the spleen of mice induced for development of EAE. Disease protection in these animals also correlated with recruitment of MDSCs to the central nervous system. Depletion of MDSCs abrogated the protective effects of α-GalCer against EAE and, conversely, adoptive transfer of MDSCs from α-GalCer-treated mice ameliorated passive EAE induced in recipient animals. The cytokines GM-CSF, IL-4 and IFN-γ, produced by activated iNKT cells, and inducible nitric oxide synthase, arginase-1 and IL-10 produced by MDSCs, contributed to these effects. Taken together, our findings have revealed cooperative immunosuppressive interactions between iNKT cells and MDSCs that might be exploited for the development of improved immunotherapies for MS and other autoimmune and inflammatory diseases.